Trade-off and synergy relationships and regional regulation of multifunctional cultivated land in the Yellow River Basin - Fang, Aman; Shi, Yuanqing; Chen, Weiqiang; Shi, Lingfei; Wang, Jinlong; Ma, Yuehong (Frontiers in Environmental Science, 2025)
Exploring the multifunctional trade-off and synergy relationship of cultivated land is of great significance for protecting cultivated land resources, ensuring food security, maintaining ecological security, and promoting high-quality development in the Yellow River Basin. Based on the selection of 379 counties with concentrated distribution of cultivated land, this study comprehensively evaluates the three-dimensional functional level of “production-society-ecology” of cultivated land from 2010 to 2020. The coupling coordination degree model, land system function trade-off degree model, and K-means clustering analysis method are used to analyze the trade-off and synergy relationship between cultivated land functions and divide the functional zones in the Yellow River Basin. 1) In the last 10 years, the levels of cultivated land production, social, and ecological functions in the Yellow River Basin are in the range of 0.01–0.47, 0.04 to 0.23, and 0.03 to 0.23, respectively. The production function is at a stable level, while the overall level of social and ecological functions has slightly improved. 2) The level of multifunctional coupling and coordination of cultivated land ranges from 0.22 to 0.65. Only 31.13% of counties have a high coupling degree between multiple functions. The production-ecological function in the upstream regions show a coordinated development trend. The social-ecological function in the midstream regions is well coordinated, and the production-social function and production-ecological function in downstream regions towards collaborative development. 3) According to the dominant functional types and the characteristics of multifunctional coupling and coordination, the cultivated land of Yellow River Basin is divided into 7 multifunctional zones, involving 149 with multifunctional advantage zones, 19 with P-S functional composite zones, 21 with P-E functional composite zones, 21 with S-E functional composite zones, 74 with social functional dominant zones, 29 with ecological functional dominant zones, 44 with grain functional dominant zones, and 22 with remediation key zones. The results can provide decision support for differentiated management of cultivated land in the Yellow River Basin and mutual promotion between functions.